The influence of soft factors on quality improvement and performance: perceptions from managers - Abdullah, Muhammad Madi; Uli, Jegak; Tari, Juan Jose (Emerald Group Publishing, 2008)
Purpose: The purpose of the paper is to investigate the influence of soft factors on quality improvement and performance and also to examine the link between quality improvement and organizational performance. Design/methodology/approach: The paper uses data from perceptions from managers in 255 electrical and electronics (E&E) firms in Malaysia and it develops regression and correlation analysis to test the relationships between soft factors, quality improvement and organizational performance. Findings: The following soft factors were found to have significant influence on quality improvement: management commitment; customer focus; employee involvement; training and education; and reward and recognition. Organizational performance was significantly influenced by the following soft factors: management commitment; customer focus; and employee involvement. Finally, this paper empirically shows that firm performance will increase when the organizations implement more quality improvement practices. Practical implications: The results of this paper can be used by managers to prioritize the implementation of the soft factors. For instance, those factors that are found to have a positive impact on quality improvement practice and performance can be recommended to managers so that they can allocate resources to improve these factors to achieve higher organizational performance. Originality/value: This paper identifies the soft factors that can influence the quality improvement practice and organizational performance in E&E Malaysian firms.